TO EVALUATION OF THE METALLOGENIC SECIALIZATION OF UKRAINIAN SHIELD GRANITOIDS - Kostenko, N.; Tolstoy, M.; Kadurin, V.; Chepijko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the basis of aggregation of three independent methods (according to absolute values of the klark concentrations of individual elements; according to the indices of concentration of the group of the typomorphic elements and appropriate accessory mineralization) defined objects in the Ukrainian Shield with a different types of metallogenic specialization